(untitled) (The International Journal for Scientific Research, 2024)
The year 1974 marked a major turning point in the history of Ethiopia, when the military seized power in a military coup that ended the 45-year rule of Emperor Haile Selassie. The famine that struck the country in 1973, along with other factors such as rising oil prices and the military defeat in Eritrea, played a significant role in paving the way for this coup. General Mengistu Haile Mariam took advantage of the popular unrest and the weakness of Haile Selassie’s regime to organize a decisive military coup on September 12, 1974, through which he overthrew Haile Selassie’s rule and formed a military council known as the “Derg” that took control of the country. The 1974 coup led to a period of political unrest and violence in Ethiopia. The Derg government pursued a strict communist policy, which led to a long and bloody civil war. Although the coup overthrew a corrupt regime, it did not succeed in bringing about the stability and prosperity that many had hoped for.